Vocational Psychology, Offenders and Ex-Offenders, and Social Justice: A Critical Psychology Perspective. (October 2013) - McWhirter, Ellen Hawley
The vocational needs of offenders and ex-offenders have received little attention in the counseling psychology literature. The authors of this special issue have called attention to the importance of and possibilities associated with the development and implementation of vocational interventions for such populations. This reaction discusses the merits of the articles in this special issue, and proposes that in addition to focusing on developing effective interventions for offenders and ex-offenders, we must interrogate the U.S. prison enterprise with respect to goals, outcomes, and ultimately, social justice.